Enhancing Students’ Literacy Competence Through Writing Bilingual Folklore Book by IT: Process Approach - Fauziah Khairani Lubis; Syamsul Bahri (RIRAI Publisher, 2021)
Writing bilingual storybooks based on local wisdom is a product of the Prose Appreciation course. The results of the evaluation so far indicate that students' low literacy skills in developing literary works such as short stories, novels, and bilingual folklore books with IT-based ISBN in 8 ethnic groups in North Sumatra. There is also a phenomenon of the influence of globalization from the use of the internet which removes boundaries between countries resulting in the spread of globalization itself which has led to increasing interest among teenagers or students towards modern literary works originating from outside Indonesia such as America, Europe, and from Asian countries. For this reason, this study will be developed to improve st udent literacy competencies through 6 types of Tasks KKNI in making IT-based ISBN-based folklore books for 8 ethnic groups in North Sumatra. Indirectly, this research explores the elements of the existing culture and is also a measure to preserve local culture. This study uses the Classroom Action Research Method (PTK). This activity is carried out through several stages of the process are a. Training in writing folklore literary works based on local wisdom in Taman Budaya. b. Review process by internal reviewers (students (peer review), and lecturers). c.Validation by internal and external expert teams. d. Publishes ISBN books of bilingual folk tales. e. Create a blog about bilingual folklore books.